12 'Recreational' consumer genomics: no such thing as a non-medical test. (4th December 2019) - Wilson, Brenda; Savard, Jacqueline; Hickerton, Chriselle; Terrill, Bronwyn; Newson, Ainsley; Gaff, Clara; Gray, Kathleen; Middleton, Anna; Metcalfe, Sylvia
Abstract : Background: The market for directly purchased personal genomic tests (PGTs) has led to their widespread availability. Their ostensible purposes include ancestry testing; educational or career planning; identifying artistic or athletic aptitudes; physical training and nutritional strategies to support fitness and wellness goals; and dating and building personal relationships. In Australia, interest in PGTs has significantly expanded in recent years. As part of the Genioz study, we explored how people personally assess the usefulness and role of PGTs in their own lives, including an examination of the boundary between 'recreational' and 'medical' aspects of genetic information. The aim of this final component of Genioz was to explore and clarify Australians' attitudes and experiences of PGTs marketed in three domains: ancestry, personal wellness, and children's health and aptitudes. We focus specifically here on implications for understanding medical issues. Methods: We conducted nine deliberative workshops across Australia, three for each domain. We recruited community-based participants for whom the PGT type would be relevant: genealogy interest, interest in personal wellness, and parenting of young children. In each workshop we used four stepped, neutrally-framed information sets to present key scientific and ethical issues, embedding pauses for facilitated discussion. We captured data using repeated tracker questions on the personal acceptability of PGT, contemporaneous unstructured written comments by participants, recording of discussions, and an end-of-workshop structured survey. Results: In total, 129 people participated, 23 with, and 106 without, personal experience of PGTs. In general, tracker responses indicated that participants seemed increasingly less comfortable with, and more thoughtful about, the pursuit of PGTs. Content analysis of discussions and written comments suggested that participants were readily able to engage with a number of ethically complex issues. The discussion data, in particular, highighted two observations about the boundary between 'medical' and 'non-medical' perspectives on PGT. Firstly, and noting the explicit non-medical PGT framing for the workshops, several participants reported that their motivation for purchasing PGTs related to 'unsolved' medical issues: representing either a continuing quest to find a 'cause' for a problem which had apparently eluded their health care practitioner, or seeking to 'prove' to their practitioner that their symptoms represented a genuine medical issue. The second observation was that some of the participants who had purchased tests – for example for ancestry tracing – had also downloaded their raw files so they could explore the data for medically relevant genetic variants. This was possible because companies routinely provide not only the information related to the original purchase (e.g. ancestry), but also - on demand - a much larger standardized dataset. A range of online applications accept data files from multiple testing companies and allow users to generate cheap, rapid reports on medically-relevant DNA variants. Conclusions: Irrespective of the original purpose, purchasing any kind of PGT allows an easy and unregulated pathway to obtaining 'medical' genetic information for the curious consumer. This 'consumer DNA screening' also offers a highway to the personal harms and system consequences of overdiagnosis.